2009
DOI: 10.1530/rep-08-0391
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte quality in lactating dairy cows fed on high levels of n-3 and n-6 fatty acids

Abstract: Different fatty acid (FA) sources are known to influence reproductive hormones in cattle, yet there is little information on how dietary FAs affect oocyte quality. Effects of three dietary sources of FAs (supplying predominantly palmitic and oleic, linoleic (n-6) or linolenic (n-3) acids) on developmental potential of oocytes were studied in lactating dairy cows. A total of 12 Holstein cows received three diets containing rumen inert fat (RIF), soyabean or linseed as the main FA source for three periods of 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 38 publications
4
72
1
4
Order By: Relevance
“…These findings strengthen the hypothesis that dietary supplementation of ω-6 and/or ω-3-fatty acids has an important role in oocyte quality and development [7]. Therefore, dietary supplementation of heifers with high levels of fish oil, which is a rich source of n-3 fatty acids, significantly increased the total amount of n-3 PUFAs and the n-3/n-6 ratio in follicular fluid [8].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings strengthen the hypothesis that dietary supplementation of ω-6 and/or ω-3-fatty acids has an important role in oocyte quality and development [7]. Therefore, dietary supplementation of heifers with high levels of fish oil, which is a rich source of n-3 fatty acids, significantly increased the total amount of n-3 PUFAs and the n-3/n-6 ratio in follicular fluid [8].…”
Section: Introductionsupporting
confidence: 82%
“…Therefore, dietary supplementation of heifers with high levels of fish oil, which is a rich source of n-3 fatty acids, significantly increased the total amount of n-3 PUFAs and the n-3/n-6 ratio in follicular fluid [8]. In the former study, alteration of PUFAs through the dietary sources of FAs led to improvement of oocyte development potential [7]. In bovine species, supplementation of maturation medium with essential fatty acids has been shown to have positive [3] or negative [4] effects on oocyte developmental competence depending on the type of fatty acid studied.…”
Section: Introductionmentioning
confidence: 96%
“…As a consequence of this, and in the absence of the differences in circulating metabolic hormone concentrations, contrasting n-3 and n-6 PUFA diets had no effect on post-fertilisation developmental potential of oocytes (Fouladi-Nashta et al 2009). Dietary FAs in that study, however, were of vegetable origin and contained relatively low amounts of long-chain bio-active PUFAs such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA).…”
Section: Introductionmentioning
confidence: 86%
“…Previous studies at our laboratory with lactating and non-lactating cattle have shown that cells within the ovarian follicle preferentially accumulate saturated FAs at the expense of PUFAs, thereby nullifying the dietaryinduced differences in PUFAs measured in plasma (Adamiak et al 2006, Fouladi-Nashta et al 2009). As a consequence of this, and in the absence of the differences in circulating metabolic hormone concentrations, contrasting n-3 and n-6 PUFA diets had no effect on post-fertilisation developmental potential of oocytes (Fouladi-Nashta et al 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Some authors reported an improved increased follicular and corpus luteum growth , oocyte (Moallem et al, 2013;Zachut et al, 2010) and embryo quality (Thangavelu et al, 2007), decreased pregnancy loss (Ambrose et al, 2006), reduced plasma prostaglandin (Petit et al, 2002), and increased serum progesterone concentration (Jahani-Moghadam et al, 2015), reduced interval from calving to ovulation (Colazo et al, 2009). In contrast, others noted no changes in milk progesterone concentration or corpus luteum activity (Ponter et al, 2006), or oocyte quality (Bilby et al, 2006, Fouladi-Nashta et al, 2009. The inconsistencies among these studies could be due to differences in the amounts of lipid supplements, duration of supplementation, and season.…”
Section: Linseed a Provider Of Omega-3 For Ruminantsmentioning
confidence: 99%